Children's experiences of meals after obesity treatment: a qualitative follow-up four years after a randomized controlled trial - Nicklas Neuman; Anna Jörnvi; Anna Ek; Karin Nordin; Karin Eli; Paulina Nowicka (BMC, 2022)
Abstract Background The practice of eating together, commensality, is rarely explored in the context of childhood obesity treatment. This is noteworthy given long-standing debates about the physical, psychosocial, and societal benefits of meals, especially family meals. Moreover, as children with obesity experience weight bias and stigma both within and outside the home, it is important to examine meals as a locus of social exchange around food and the body. Our study is based on the premises that eating together (i) matters and (ii) occurs in different environments with diverse social organization, where food-related interactions create varying arrangements of individuals, groups, their statuses, and their actions. Method The study explores children's experiences of meals in different social contexts. Thirty-two children (age 8-10 years) living in Sweden were interviewed, 4 years after they entered an obesity intervention trial. Thematic analysis was applied to the data. Results We thematized three meal types, with each meal type having two subthemes: (i) "The family meal", with "Shared routines, rituals, and rules" and "Individual solutions and choices"; (ii) "The school meal", with "Rules and norms of the school" and "Strategies of the child"; and (iii) "The friend meal", with "Handling food that was disliked" and "Enjoyment of food". These three different meal types carried different experiences of and knowledge about how they were socially organized. Conclusions While the children spoke about the family and school meals as meaningful, the friend meal stood out as particularly positive. Contrary to our expectations, the children did not express experiences of weight bias or obesity stigma around meals, nor did they speak negatively about parental control of their food intake. Our findings, especially regarding the friend meal, have implications for further research into commensality and social influences on eating among children with obesity, from early childhood into adolescence.